(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: To describe the characteristics of the seminiferous tubules and the relationship to sperm collection by micro-TESE (Microdissection testicular sperm extraction - micro TESE) in patients with nonobstructive azoospermia (NOA). Subjects and research methods: 132 NOA patients were performed micro TESE at the Military Clinical Embryo Institute - Vietnam Military Medical University from 5/2017 to 12/2019. Results: Histopathology of 132 NOA patients showed that the rate of hypospermatogenesis (HP), maturation arrest (MA), Sertoli cell only syndrome (SCOS) and hyalinization was 8.33%, 20.45%, 59.85%, and 11.36%, respectively. The diameter of the seminiferous tubules in patients with NOA was smaller than the normal value, in which the fibrous sheath thickness was thicker. The epithelial cells reduced severely. The percentage of patients with sperm collection was 40.15%. The probability of finding spermatozoa in patients with normal seminiferous tubule diameter and fibrous sheath thickness was 5.58 times and 6.20 times compared with patients out of the normal values. The probability of finding spermatozoa in patients with Johnsen score ≥ 8 was 6.66 times higher than that in patients with Johnsen score < 8. Conclusion: There was a difference in characteristics of the seminiferous tubules in NOA patients compared with the normal value. Histopathology is one of the factors predicting the success of the micro TESE method. There was a relationship between seminiferous tubule diameter, fibrous sheath thickness and Johnsen score to sperm collection rate in NOA patients.